Dipeptide end-capping resultant multiple hydrogen bonds triggering self-healing waterborne polyurethane elastomers. (19th April 2022) - Zhang, Ning; Pan, Zhicheng; Li, Chao; Wang, Juan; Jin, Yao; Song, Shaofeng; Pan, Mingwang; Yuan, Jinfeng
Abstract: Self-repairing materials with damage self-healing ability have attracted much attention because of their potentials to improve the reliability, durability, and life of materials. However, its poor self-repair performance in the ambient environment still faces the challenge for waterborne polyurethane (WPU) broad range of applications. In this work, to break through the limitation of chain stiffness and improve the self-healing ability, we choose glycylglycine methyl ester as a functional end-capping reagent to seal the WPU chain (WPUG) and provide triple intermolecular hydrogen bonds. It is found that the chain-end triple hydrogen bonds act a unique role in WPUG, which can serve as a "bridge" to connect soft segments, endowing the molecular chain with more flexibility and fluidity. As a result, the self-healing efficiency of WPUG in the surrounding environment can reach 91.5% within a short time. This work suggests a new point of view on the role and interaction mechanism of chain-end hydrogen bonding in WPUs. Graphical abstract: Image 1 Highlights: Water-borne polyurethane is an environment-friendly material. Dipeptide capping the chain-end resulting in multiple hydrogen bonds. Dipeptide provides chain-end hydrogen bonds to form "bridge" structure. Hydrogen bonds endow the chain with greater flexibility and liquid-like flowability. Dipeptide improves the self-healing ability of elastomers at ambient temperature.